Markov Property Analysis of the Real-World Driving Data and Its Application - Nguyen, Thi Yen Lien; Nghiem, Trung Dung (Old Journal, 2018)
There are a number of methods that can be used for the development of a driving cycle. Among them, the Markov chain is a promising approach which has been being widely studied in recent years in many developed countries but still is scarce in Vietnam. In this study, the real-world driving data of bus system in Hanoi are proved to be a stationary time-series and have the Markov property, based on the analysis of random number series which are the values of instantaneous speed of the bus recorded by the GPS in a whole bus route. The typical driving cycle of the bus route No.9 was then developed based on this finding. The developed cycle was assessed in the comparison with the on – road driving data. A good conformity of this driving cycle with the real –world driving data was observed.